The Role of Court Experts in Protecting the Interest of the Child in Domestic Civil Procedures - Danuta Anna Michałowska (Acta Universitatis Lodziensis Folia Iuridica)
In court procedures, the role of court experts and their opinions is important for the final decisions. It is generally accepted that the court appoints experts and makes decisions based on – among other things – specialised expertise and opinions of these experts. Court experts’ knowledge differs from that of judges. It is worth analysing the intersections between these two types of knowledge. In this context, special attention is to be paid to the position and status of the child in court proceedings in family matters. The main purpose of this article is to examine the role of court experts in safeguarding children’s best interests in civil procedures within the family matters context, which can help to improve the understanding of and trust in court experts’ contribution from the institutional and societal perspective.